Copula-based risk evaluation of hydrological droughts in the East River basin, China - Zhang, Qiang; Xiao, Mingzhong; Singh, Vijay P; Chen, Xiaohong (Stochastic environmental research and risk assessment, 2013)
Probabilistic characteristics of hydrological droughts in a basin are closely related to the variability and availability of water resources of the basin. The East River basin in China is the main source for water supply for mega cities in the Pearl River Delta and cities in the vicinity of the Delta, such as Hong Kong. The water supply is subject to the vagaries of weather and water resources in the basin exhibit probabilistic characteristics. Using daily streamflow data for a period of 1975–2009 from 4 hydrological stations in the East River basin, this study attempts to determine probabilistic characteristics of hydrological droughts using copula functions. The bivariate quantile curves of the secondary return periods for hydrological drought of all the hydrological stations have been built and the results a higher risk of hydrological droughts in the upper East River basin. Furthermore, water resources should be managed by considering the entire East River basin in order to sustain the regional socio-economic development, and the extreme value copula has been used to describe the extreme drought events in the East River basin.